Analysis of Local Government Response to Floods in Aceh: Netnography Approach - Dafit Hidayat; Nur Fitriani Wulandari; Aldila Hisyam Hasrudin; Ovalia Rukmana (CV. Publikasi Indonesia, 2026)
The major floods that hit Aceh Province in November 2025 had a significant impact on the social, economic, and infrastructure lives of people in various districts. The disaster management places local governments as the main actors in the emergency response phase, especially in evacuation, logistics distribution, cross-agency coordination, and crisis communication. This study aims to analyze the response of the Aceh local government to the November 2025 floods and identify the factors that affect the effectiveness of the response. This study uses a qualitative approach with a case study design. Data was collected through analysis of official government documents, online media reports, and social media content of people affected by the floods. Data analysis was carried out using thematic analysis to identify government response patterns, field constraints, and crisis communication dynamics. The results of the study show that the response of local governments is relatively fast in urban areas with good transportation access. However, there have been significant delays in isolated areas due to infrastructure damage and limited coordination. In addition, the mismatch between the government's official narrative and the conditions on the ground has an impact on declining public trust. On the other hand, the resilience of local communities plays a key role as a buffer in the early phases of disasters through self-evacuation initiatives and community solidarity. This study concludes that the effectiveness of local government responses in flood management is influenced by regional access factors, disaster management governance, and the quality of crisis communication. Strengthening cross-agency coordination, empathetic communication strategies, and integrating the role of local communities are the main recommendations to improve disaster management in the future.